Harnessing structurally unbiased ortho-benzoquinone monoimine for biomimetic oxidative [4+2] cycloaddition with enamines. Issue 44 (29th April 2020) - Bashir, Muhammad Adnan; Zuo, Honghua; Lu, Xunbo; Wu, Yuzhou; Zhong, Fangrui
Abstract : Reported herein is the first catalytic oxidative [4+2] cycloaddition of 2-aminophenols with cyclic enamines. Abstract : Reported herein is the first catalytic oxidative [4+2] cycloaddition of 2-aminophenols with cyclic enamines. This biomimetic catalytic oxidative strategy expediently accommodates the very labile structurally unbiased ortho -quinone monoimine intermediate for cycloaddition by controlling its formation rate, thus refraining from otherwise prerequisite steric or electronic stabilization and allowing efficient assembly of various tricyclic 1, 4-benzoxazines in a step and atom economic fashion.